Efficacy of metal nanoparticles as a control tool against adult mosquito vectors: A review - Blore, Kai; Baldwin, Rebecca; Batich, Christopher D.; Koehler, Phillip; Pereira, Roberto; Jack, Cameron J.; Qualls, Whitney A.; Xue, Rui-De (Frontiers in Tropical Diseases, 2022)
Presently, there is a need to develop effective and novel modes of control for mosquitoes, which remain a key driver of infectious disease transmission throughout the world. Control methods for these vectors have historically relied on a limited number of active ingredients (AIs) that have not experienced significant change in usage since the mid-20th century. The resulting development of widespread insecticide resistance has consequently increased the risk for future vector-borne disease outbreaks. Recently, metal nanoparticles have been explored for potential use in mosquito control due to their demonstrated toxicity against mosquitoes at all life stages. However, the majority of studies to date have focused on the larvicidal efficacy of metal nanoparticles with few studies examining their adulticidal potential. In this review, we analyze the current literature on green synthesized metal nanoparticles and their effect on adult mosquitoes.